Pengelolaan Sampah Menjadi Nilai Ekonomis Melalui Bank Sampah Di Desa Salam, Gebang, Purworejo - Harayo, Recika Ranna; Hidayati, Dwi Nuril; Nurlaelasari, Fenny; Ngazizah, Nur (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Trash is used goods that are no longer used by the community. Waste is considered to have no use value, so it is often considered trivial by society. The Sejahtera Waste Bank is a place to collect waste from local residents which was established in 2020 and is managed by young residents of Salam Village to create a beautiful environment and manage waste so that it has economic value. This research uses descriptive research with a qualitative approach. Qualitative descriptive research is a research approach by collecting data sourced from interviews and documentation. The results obtained by Bank Sampah Sejahtera carry out waste processing activities into handicrafts that have economic value, one of which is training in making flowers from plastic plastic waste. The benefits obtained are a beautiful environment, no littering, and opening up employment opportunities.